2020
DOI: 10.1186/s13027-020-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Host proteome linked to HPV E7-mediated specific gene hypermethylation in cancer pathways

Abstract: Background: Human papillomavirus (HPV) infection causes around 90% of cervical cancer cases, and cervical cancer is a leading cause of female mortality worldwide. HPV-derived oncoprotein E7 participates in cervical carcinogenesis by inducing aberrant host DNA methylation. However, the targeting specificity of E7 methylation of host genes is not fully understood but is important in the down-regulation of crucial proteins of the hallmark cancer pathways. In this study, we aim to link E7-driven aberrations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…To further evaluate the in vivo CIGB-300-E7 interaction between both molecules, we performed in vivo pull-down. We employed HEK293 as an epithelial cell model with high transfection efficiency that has been previously used for studying E6 and E7 interaction partners [ 37 ]. Using HEK293 cells overexpressing HPV-16 E7, we observed physical interaction between CIGB-300 and E7 protein.…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluate the in vivo CIGB-300-E7 interaction between both molecules, we performed in vivo pull-down. We employed HEK293 as an epithelial cell model with high transfection efficiency that has been previously used for studying E6 and E7 interaction partners [ 37 ]. Using HEK293 cells overexpressing HPV-16 E7, we observed physical interaction between CIGB-300 and E7 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was hypothesized that there would be genes other than CCNA1 and CADM1 whose promoters are methylated by HPV 16 E7, and that there would be specific transcription factors binding with HPV 16 E7 on the gene promoter. A study by Na Rangsee et al ,used STRING database protein network analysis, showed that E7 possibly forms a complex with the set of transcription factors containing a YY1 domain ( 26 ). In the present study, the binding site of HPV 16 E7 on the CCNA1 promoter was analyzed to identify the putative transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their study indicated that the E7 protein can bind to the promoter region of CADM1 , and chromatin immunoprecipitation indicated that it may bind to DNMT1 through the same mechanism as CCNA1 ( 25 ). Na Rangsee et al ( 26 ), using readings from mass spectrometry followed by STRING database protein network analysis, showed that E7 possibly formed a complex with a set of transcription factors, including SP1, which links with the Yin yang 1 (YY1) transcription factor contributing to the E7 mediated hypermethylation of the genes. This highlighted the possibility of E7 combining with DNMT1 through a transcription factor to the promoter region of the CCNA1 gene, resulting in promoter methylation.…”
Section: Introductionmentioning
confidence: 99%
“…These changes in DNMT1 activity have effects on other downstream targets critical in tumorigenic pathways, including E-cadherin and cyclin A1 45,46 , and may be responsible for the intragenic CDKN2A methylation we observed in this study. It is also likely that additional oncoproteinmediated alterations in gene expression are linked to host DNA methylation 47 .…”
Section: Alsomentioning
confidence: 99%